2006
DOI: 10.1039/b606432a
|View full text |Cite
|
Sign up to set email alerts
|

A hydrophilic interaction chromatography coupled to a mass spectrometry for the determination of glutathione in plant somatic embryos

Abstract: An electrospray ionization mass spectrometric (ESI-MS) determination of glutathione (GSH), a sulfur-containing tripeptide (gamma-Glu-Cys-Gly) with regulation and detoxication functions in metabolisms of most living organisms, from nanomolar to micromolar levels is described. A hydrophilic interaction chromatography (HILIC) with an isocratic elution using a mobile phase containing acetonitrile and an aqueous 0.00005% solution of trifluoroacetic acid (60/40%, v/v) was applied for the separation of GSH. The pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 60 publications
0
39
0
1
Order By: Relevance
“…Very few publications can be found for HILIC separation of amino acids and peptides coupled online to ESI-MS. The determination of glutathione in plant somatic embryos was successfully achieved with low detection limit (0.5 nM), high selectivity and reproducibility, promising its application in microscopic cell structures and in single cell analyses [115]. Langrock et al [116] showed that a method could separate and detect three isobaric amino acids, Hyp-isomers, Ile, and Leu, allowing an unambiguous identification of amino acids.…”
Section: Biomolecular Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…Very few publications can be found for HILIC separation of amino acids and peptides coupled online to ESI-MS. The determination of glutathione in plant somatic embryos was successfully achieved with low detection limit (0.5 nM), high selectivity and reproducibility, promising its application in microscopic cell structures and in single cell analyses [115]. Langrock et al [116] showed that a method could separate and detect three isobaric amino acids, Hyp-isomers, Ile, and Leu, allowing an unambiguous identification of amino acids.…”
Section: Biomolecular Analysismentioning
confidence: 98%
“…This leads to the possibility in studying the function of such metabolites. Additionally, several other analyses of plant extracted metabolites have been performed, including phytosiderophores and their metal complexes on a ZIC column [129], and glutathione on a silica column [115]. However, in some cases as indicated by Su et al [130], successful determination of metabolites is not enough to completely elaborate a complex metabolism mechanism.…”
Section: Metabolic Studiesmentioning
confidence: 98%
“…The analytical methods for determination of GSH and other bioorganic small thiols are based on instrumental techniques including spectrophotometry (Rusin et al, 2004;Tanaka and Mase, 2004;Wang et al, 2005), electrochemical voltammetry (Ndamanisha et al, 2009;Pacsial-Ong et al, 2006;Spãtaru et al, 2001;Stobiecka et al, 2009), HPLC (Lu et al, 2007;Vacek et al, 2006;Zhang et al, 2005), and colorimetric sensors (Huang et al, 2010;Kou et al, 2007;Lim et al, 2008;Sudeep et al, 2005;Uehara et al, 2010;Zhang et al, 2002). Recently, surface-assisted laser desorption/ionization mass spectrometry has been proposed for the analysis of GSH in cell lysates (Chiang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Standard kits usually rely on spectrofluorimetry (Meyer et al 2001;Xu et al 2015) and ELISA (antigen-antibody recognition) and reach limits of detection around 0.1-0.5 µg/mL (0.325-1.625 µM). Other techniques such as electrochemistry (Harfield et al 2012;Ndamanisha et al 2009;White et al 2002), high-performance liquid chromatography (Lu et al 2007;Vacek et al 2006;Zhang et al 2005), gas chromatography (Kataoka et al 1995), or quartz crystal microbalance (Gerdon et al 2005) have been employed enabling the detection at lower levels. However, all these methods have advantages but also drawbacks, such as less selectivity against other aminoacids or the time consuming characteristics, that make the analysis tedious and complicated.…”
Section: Introductionmentioning
confidence: 99%